Habitus Santri Ndalem: Analisis Khodam Kyai PP Al-Qodiri Jember pada Kesalehan Ekologis - syaiful rizal (STIS MIFTAHUL ULUM LUMAJANG PRESS (STISMU PRESS), 2023)
Stage 4 is an appropriate expression for the current ecological situation, a precarious situation for humans and their foundation, namely the earth, which is threatened with extinction. Islam teaches a life in harmony with nature. Not a few hadiths and verses that convey about the environment. Santri who study or enter pesantren also have different motivations, one of which is to become khodam kyai. The focus in this research is what Islamic values ​​are used as the spirit of khodam kyai and how is the habitus of khodam kyai PP Al-Qodiri Jember on ecological piety? To describe the focus of the research, this study uses qualitative research methods with a phenomenological approach, porposive sampling and interpretive phenomenological analysis (IPA) data analysis. From the use of the method above, the results of his research show that: 1) Islamic values ​​are used as the spirit of khodam kyai PP Al-Qodiri Jember on ecological piety, namely originating from Islamic teachings and their caregivers. The Islamic values ​​that are used as the spirit of khodam kyai PP Al-Qodiri on ecological piety are the Islamic values ​​of qodarullah, khalifatul fil ardy wa Rahmatan Lil Alamin, worship, blessings and self-cleaning. 2) the habitus form of khodam kyai PP Al-Qodiri Jember on ecological piety namely Muhasabah (self-evaluation), muroqobah (closeness to nature lovers), muadadah (unity), Tadabbur alam (learning from nature), and Istiqomah (consistency). Keywords: Habitus, Khodam kyai, Ecological Piety